2019
DOI: 10.34297/ajbsr.2019.04.000810
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Bangladeshi Children and Adolescents of Affluent Families by Level of Obesity

Abstract: This work is licensed under Creative Commons Attribution 4.0 License AJBSR.MS.ID.000810

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This analysis indicated that the levels of BMI of the adults were significantly different according to the differences in the levels of residence, gender, age, education, occupation, income, smoking habit, marital status and prevalence of non-communicable diseases. This finding was also similar to those were observed earlier [ 18,19,[22][23][24][25].…”
Section: Some Results Of Analysis Of Variancesupporting
confidence: 93%
“…This analysis indicated that the levels of BMI of the adults were significantly different according to the differences in the levels of residence, gender, age, education, occupation, income, smoking habit, marital status and prevalence of non-communicable diseases. This finding was also similar to those were observed earlier [ 18,19,[22][23][24][25].…”
Section: Some Results Of Analysis Of Variancesupporting
confidence: 93%
“…As another example the analytical results obtained from the data collected from 900 adults of Bangladesh [18,19] were presented here. This analysis indicated that the levels of BMI of the adults were significantly different according to the differences in the levels of residence, gender, age, education, occupation, income, smoking habit, marital status and prevalence of non-communicable diseases.…”
Section: Some Results Of Analysis Of Variancementioning
confidence: 99%
“…For example, age, height, weight, gender, marital status, religion, education, occupation, income, food habit, working conditions, smoking habit, and utilization of time are associated with many noncommunicable diseases. This phenomenon was observed in many studies, home and abroad [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], especially these characteristics were found associated with level of obesity, prevalence of diabetes and prevalence of other non-communicable diseases. The level of obesity is measured by the ratio of body weight (in kg) to square of height (in m 2 ).…”
Section: Introductionmentioning
confidence: 83%
“…Among urban Bangladeshi school children researchers also found high consumption of fast foods and sugary drinks and low consumption of fruits, vegetables and animal source food [17,18]. However, little is known about the contextual drivers of these food choices.…”
Section: Introductionmentioning
confidence: 99%